2001
DOI: 10.1128/jvi.75.18.8649-8659.2001
|View full text |Cite
|
Sign up to set email alerts
|

Differential Immunogenicity of Epstein-Barr Virus Latent-Cycle Proteins for Human CD4+T-Helper 1 Responses

Abstract: Human CD4 ؉ T-helper 1 cell responses to Epstein-Barr virus (EBV) infection are likely to be important in the maintenance of virus-specific CD8؉ memory and/or as antiviral effectors in their own right. The present work has used overlapping peptides as stimulators of gamma interferon release (i) to identify CD4 ؉ epitopes within four EBV latent-cycle proteins, i.e., the nuclear antigens EBNA1 and EBNA3C and the latent membrane proteins LMP1 and LMP2, and (ii) to determine the frequency and magnitude of memory r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
211
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 209 publications
(220 citation statements)
references
References 50 publications
9
211
0
Order By: Relevance
“…EBNA-1-specific CD4ϩ T cells (45,46), mainly of the Th1 phenotype (47), have recently been detected in healthy EBV carriers and may provide help for the production of antibodies directed to the different epitopes of this protein. In the presence of a higher EBV load, events such as apoptosis, infection, damage, or any stimulus involving calcium influx may activate PAD, which is highly expressed in RA synovia (48,49), and induce the deimination of different proteins, including viral proteins.…”
Section: Discussionmentioning
confidence: 99%
“…EBNA-1-specific CD4ϩ T cells (45,46), mainly of the Th1 phenotype (47), have recently been detected in healthy EBV carriers and may provide help for the production of antibodies directed to the different epitopes of this protein. In the presence of a higher EBV load, events such as apoptosis, infection, damage, or any stimulus involving calcium influx may activate PAD, which is highly expressed in RA synovia (48,49), and induce the deimination of different proteins, including viral proteins.…”
Section: Discussionmentioning
confidence: 99%
“…23,33,34 Furthermore, our recent studies have shown that LMP1 and LMP2 are also a poor source of epitopes for the CD4 ϩ T cell response. 35 Why these molecules should be relatively poorly immunogenic is not understood. In the case of LMP1, it may be that the protein itself has immunosuppressive properties that favor the induction of T cell anergy.…”
Section: Discussionmentioning
confidence: 99%
“…EBV nuclear antigen 1 (EBNA-1) is a latent antigen that is invariably expressed in all EBV-infected proliferating cells [16] and associated malignancies [17], being crucial for viral persistence by acting as replication and transcription factor [18], without viral particle formation. EBNA-1 is an immunodominant latent target of EBVspecific CD4 1 T cells [19,20]. Although it has been described in the past to escape from recognition by CD8 1 T cells due to Gly/Ala repeated domains preventing proteasome-dependent processing for presentation on MHC class I [21], more recent studies revealed the existence of EBNA-1-specific CD8 1 T cells [15,22,23].…”
mentioning
confidence: 99%